Characterization of the Antinociceptive Mechanisms of Khat Extract (Catha edulis) in Mice - Afify, Elham A.; Alkreathy, Huda M.; Ali, Ahmed S.; Alfaifi, Hassan A.; Khan, Lateef M. (Frontiers in Neurology, 2017)
This study investigated the antinociceptive mechanisms of Khat extract (100, 200 and 400 mg/Kg, i.p.) in four pain models; two thermic (hot plate, tail flick) and two chemical (acetic acid , formalin). Male mice were pretreated intraperitoneally (i.p.) with the opioid receptor blocker naloxone (5 mg/Kg), the cholinergic antagonist atropine (2 mg/Kg), the selective α1 blocker prazosin (1mg/Kg), the dopamine D2 antagonist haloperidol (1.5 mg/Kg), or the GABAA receptor antagonist, bicuculline (1mg/Kg) 15 minutes prior to i.p. injection of khat extract (400 mg/Kg). Khat extract reduced the nociceptive response of mice in the four pain tests. Naloxone significantly inhibited the antinociceptive effect of khat extract in the hot plate, tail flick and the first phase of formalin tests. Bicuculline significantly antagonized the antinociceptive effect of khat extract on the hot plate and tail flick tests. Haloperidol significantly reversed the antinociceptive effect of khat extract on the tail flick test and the first phase of formalin test. These results provide strong evidence that the antinociceptive activity of khat extract is mediated via opioidergic, GABAergic and dopaminergic pathways. The mechanism of the antinociceptive action of khat may be linked to the different types of pain generated in animal models. Keywords: Khat (Catha edulis), Hot plate, formalin, Tail flick, Opioidergic, dopaminergic, GABAergic .